FRI0082 SLEEP PROBLEMS IN EARLY RHEUMATOID ARTHRITIS. (13th June 2020) - Lehtonen, T.; Åkerstedr, T.; Lyne, L.; Klareskog, L.; Saevarsdottir, S.; Alfredsson, L.; Westerlind, H.
Abstract : Background: It is well known that patients with established RA suffer from problems with sleep quality[1]. There are however few, if any, studies on sleep quality among newly diagnosed patients. Objectives: To investigate the sleep quality among patients newly diagnosed with RA. Methods: We used the Swedish study Epidemiological Investigation of RA (EIRA) including patients at the time of diagnosis, based on the 1987 ACR criteria during 2008-2016. At 1 and 3 years after diagnosis, the patients were sent a questionnaire in which they were asked to rate their sleep quality on 10 different questions. We then calculated 6 different sleep components consisting of insomnia, non-restorative sleep, sleep problems, general quality of sleep, if poor sleep affected the health and if they were getting enough sleep[2]. Sleep problems were defined as mostly or always having problems with either of the following: falling asleep, many awakenings with difficulties to go back to sleep, waking up early or having disturbed/restless sleep. Insomnia was defined as answering mostly or always on either problem with falling asleep, many awakenings with difficulties to go back to sleep or waking up early, in combination with mostly or always being tired during the day. Having problems with non-restorative sleep was defined as mostly or always having trouble waking up or not feeling well rested when waking up. We defined having problem with not getting enough sleep, sleep quality affecting the health and poor sleep quality as reporting any of the two highest scores on the corresponding questions. We then calculated the proportion of people experiencing no problems at 1 or 3 years after RA diagnosis, developing problems, improving or always having problems with their sleep. Results: We identified 1483 patients with data at either one or both time points. The mean age was 59 years (IQR 19), and 1063 (72%) were women. At 1 year, 36% of the patients reported having at least one type of sleep problem, after 3 years, this figure was 29%. Over 20% of the patients reported having "Rather big" or "Very big" problems with sleep after one year (Table 1 ) and 31% had problems at one or both time points (Table 2 ). Disturbed sleep was a problem for their health in 20% of the patients and 11% reported having "poor" or "very poor" sleep quality at both times. Insomnia was experienced by 118 (10%) patients at 1 year and 112 (11%) at 3 years. Conclusion: In a population-based early RA cohort receiving today's standard care, 30% of the patients reported some type of sleep problem during the first 3 years. Although this is a lower rate than has been reported in established RA, this is a significant proportion of RA patients, and these findings warrant further studies to closer identify the course of sleep problems and the factors influencing it such as pain. References: [1]Bourguignon C et al PMID 14596374 [2]Akerstedt T et al PMID 18484368 Acknowledgments: The authors wish to acknowledge the EIRA study group and the EIRA data collectors. Disclosure of Interests: Tiina Lehtonen: None declared, Torbjörn Åkerstedr: None declared, Lauren Lyne: None declared, Lars Klareskog: None declared, Saedis Saevarsdottir Employee of: Part-time at deCODE Genetics/Amgen Inc, working on genetic research unrelated to this project, Lars Alfredsson: None declared, Helga Westerlind: None declared